Efektivitas Perbedaan Metode Pembelajaran Quiz Team Dengan Metode Pembelajaran STAD Terhadap Minat dan Hasil Belajar Siswa Pada Mata Pelajaran di SMPN 1 Jerowaru - Irwan Yon Hadi (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
This research is an experimental type that aims to determine the differences in the use of the Quiz Team learning method with the STAD learning method on interest and learning outcomes. The subjects of this study were 63 students of class VIII of SMPN 1 Jerowaru. The sample in this study was 61 students of class VIII of SMPN 1 Jerowaru, experimental class I using the Quiz Team learning method and experimental class II using the STAD learning method. Data collection techniques used questionnaire and test techniques. Data analysis techniques used normality tests, homogeneity tests and hypothesis tests using the t-test formula. The results of the study obtained from the average value of learning interest for experimental class I = 64.5333. While for experimental class II the average value = 58.0323, there is a difference or difference in the average value between experimental class I and experimental class II of 6.501 and the results of the hypothesis test using the t-test formula = 5.8098. And the results of the study obtained from the average value of learning outcomes for experimental class I = 83.4667, while for experimental class II = 80.87097, there is a difference or difference in the average value between experimental class I and experiment II of 2.59573. The results of the hypothesis test of the learning interest variable using the t-test formula = 5.8098, while the results of the hypothesis test of the learning outcome variable using the t-test formula = 2.0414. From the results of the study it can be concluded that there is a significant difference using the Quiz Team learning method with the STAD learning method on the interests and learning outcomes of class VIII in integrated social studies subjects at SMPN 1 Jerowaru.